NAHDLOTUL ULAMA’ DAN PILKADA KABUPATEN TUBAN 2020 - Sri Musrifah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the participation of Nahdlotul Ulama' (NU) in the regional head election (Pilkada) of Tuban Regency 2020. Through a participation approach, located in the PKB DPC of Tuban Regency, the NU DPC of Tuban Regency and the Tuban Regency KPU, qualitative and in-depth methods were used. dept-interview, direct observation and documentation in data collection. With informants of Nahdlotul Ulama cadres who occupy public positions (chairman of the Tuban Regency DPRD, members of KPU commissioners and lecturers). This research results in an analysis that Nahdlotul Ulama' (NU) will remain a socio-religious organization, but frees its cadres from politics, actively participates in the Tuban district election stage, in the sense of personal politics. Keywords: Nahdlotul Ulama', Pilkada, Tuban Regency